Non-linear cointegration and adjustment: exponential smooth-transition model for Malaysian export demand - Duasa, Jarita (Serials Publications, 2012)
The present study attempts to analyze the long-run equilibrium relationship between real exchange rate and export demand by non-linear cointegration tests. The Engle-Granger two-step cointegration test is expanding to incorporate an exponential smooth-transition error correction term (ESTAR model) as it is expected that there might be non-linear adjustment aroused according to the size of the disequilibrium. Using Malaysian data of export volume and real exchange rate, the estimation of the model supports non-linear reversion to equilibrium when deviations from equilibrium become sufficiently large. The results reflect that any export deviation/shock, either positive or negative, is only be temporary once the deviation is sufficiently large as the speed of adjustment to the long-run value will be faster than when it is small in size. It is perceived that this dynamic movement of exports is due to extensive policy instruments used by Malaysian authority on exports which aim at sustainable economic growth to attain national vision of being a developed country in 2020.